Fintech As Financial Inclusion : Effect of FinTech on the share price and profitability of commercial banks in Malaysia, Indonesia and Singapore. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The technological industry has advanced so much that it has changed the way people get things done. The growth of FinTech companies worldwide poses a threat to the retail banks since Fintech provides better alternatives to banks at the comfort of our own homes. The objective of this research is to find the effect FinTech has on the banking industry of Malaysia, Singapore and Indonesia. The main variables that are studied are profitability and the share price of the banks. A study as such is much needed in South East Asia since fewer research has been made on this topic. The data has been collected from two of the top commercial banks in each of the countries. A total of six banks has been included in this research and the data dates to a 5 year time period between 2015 and 2019. The findings reveal that there is a positive impact on the profitability of the banks. However, the share price keeps fluctuating from year to year, which is why we cannot come to a conclusion whether it is caused by FinTech since many other factors are involved as well.